The role of culture and cultural context : a mandate for inclusion, the discovery of truth and understanding in evaluative theory and practice - Hood, Stafford; Hopson, Rodney K.; Frierson, Henry T. 1944- (Emerald Publishing Limited : IAP, 2005)
This volume seeks to address select questions drawn from the matrix of the complex issues related to culturally responsive evaluation. We ask, should evaluation be culturally responsive? Is the field heading in the right direction in its attempt to become more culturally responsive? We ask, what is culturally responsive evaluation today and what might it become tomorrow? This edited volume does not promise to deliver answers to all, most, or even many of the complex answers facing the evaluation community regarding the role of culture and cultural context in evaluative theory and practice. This is not a scientific undertaking. We are not ready for concerns with prediction, explanation or control. We are ready for serious explorations, however. Even if the evaluation community cannot articulate the necessary and sufficient conditions for a culturally relevant evaluation it does know several of the desiderata. Our concern and the direction of this volume has been reflections of evaluation theory, history, and practice within the context of culture with illustrative examples.
Keywords: Educational evaluation -- Social aspects -- United States.; Educational equalization -- United States.; Education -- Evaluation & Assessment.; Education: examinations and assessment.; elektronické knihy; electronic books